Skoring dan Interpretasi dari Group Management Questionnaire Untuk Menilai Efektivitas Tim Para Pekerja - Denissa, Syafina; Hadi, Cholichul; Dwi, Giovanny; Intania, Tiara; Christina, Sarah (Jurnal Syntax Fusion, 2023)
The Group Management Questionnaire (GMQ) is an instrument that requires each team member to respond to seventy-two positive statements, all of which have proven to be important for an effective team. Because this instrument is quite good and can provide an overview of an effective team, the authors suggest using this instrument for workers who work in teams within the organization at their company to measure the effectiveness of their team members at work which can then be reviewed about the extent to which the team members can be effective based on the 8 categories in the GMQ. The author suggests it because based on the literature, during the Covid-19 pandemic, there were still several workers who were members of their teams/divisions who were less productive and felt that their performance was not good because there was a mental influence on them. Coupled with the post-pandemic crisis that requires organizations to rise, of course, the effectiveness of a team must be further improved.